Brown spot of pear, an emerging disease in Argentina: identification and pathogenicity characterization of Argentinean Stemphylium vesicarium isolates - Temperini, Carolina Virginia (2022)
Recently, a new plant disease was detected in the rural area of the High Valley of Río Negro, in Northern Patagonia, Argentina, called “Brown Spot of Pear” (BSP), caused by Stemphylium vesicarium (teleomorph: Pleospora herbarum, syn. Pantoea allii) in its sexual and asexual stages which produces lesions on leaves and fruits. BSP has been reported previously in pear growing areas of Europe and Japan where research studies have assessed the production of two host-specific toxins (HSTs) in culture filtrates of S. vesicarium (SV-I and SV-II toxin). The purpose of the present study was to characterize Stemphylium isolates from air and from brown spot lesions on pear leaves and fruits grown in this rural area, at a morphological, molecular and pathogenic level. The pathogen’s identity was determined as S. vesicarium and its aggressiveness and toxicity were demonstrated through conidia and culture filtrate bioassays showing different degrees of pathogenicity. D’Anjou and Abate Fetel were the most susceptible pear cultivars to S. vesicarium isolates.